Analisis Kelayakan Limbah Keramik Sebagai Pengganti Agregat Halus Untuk Campuran Aspal Beton - Ali, Muhammad Chaeder; Nurdin, Abdul Rahim; Yunus, Ahmad Yauri (Program Studi Teknik Sipil Universitas Bosowa, 2024)
Asphalt concrete is an even mixture of aggregate and asphalt as a binder. Before mixing, the two ingredients must be heated to dry the aggregate and get a sufficient liquid level of asphalt to make the mixture easy. Ceramic waste can be used as an alternative aggregate in asphalt concrete mixtures. They must be ground until they meet the standard fine aggregate grain diameter. The objective of this research is to evaluate that the fine aggregate samples studied are crushed ceramic waste; to evaluate ceramics used as fine aggregates in hot asphalt mixes that meet asphalt concrete quality standards; and to evaluate the properties of hot asphalt that uses ceramic waste as fine aggregates. I chose the title of this research because ceramic waste improves asphalt concrete's quality. The research uses the Marshall testing method, which is meant to determine the resistance (stability) to plastic melting (flow) of the asphalt and aggregate mixture. The asphalt concrete mixture uses a variety of ceramic waste fine aggregates of 100%, 75%, 50% and 25%. With The 100% ceramic waste asphalt mix had the highest Marshall stability value, with an average of 1561.07 kg; the 25% ceramic waste asphalt mix had the lowest, with an average of 1548.31 kg.